Mental Health and Resilience in Women Victims of Domestic Violence - Raissa Patrisia; Irma (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
Domestic violence against women has become an open secret. Some so many women experience violence that causes various losses both physical, psychological, and financial. The purpose of this study was to determine the impact of domestic violence on women's mental health and resilience. The method used in this study is qualitative. Based on the results of the study, it was found that all participants experienced physical, verbal, and sexual violence that affected their resilience. The participants took longer to recover from the trauma and pain of violence from their partners. Social support plays an important role in helping women victims of violence to recover and seek help. An interesting condition of the participants was their financial dependence on their husbands. This makes the husband feel more powerful and does not respect the wife. In addition, the low level of education causes them to lack understanding of the existence of laws that protect them from violence and difficulty seeking help on their own